The complete chloroplast genome of Securigera varia (L.) Lassen. Issue 3 (4th March 2021) - Zhao, Yi; Xi, Qianqian; Wei, Xiangyu; Fu, Jiayi; Wang, Qianqian; He, Hongyan; Ling, Chen; Chang, Tianliang; Zhao, Yuwei
Abstract: Securigera varia is an important leguminous forage grass species that is mainly distributed in arid and semi-arid land with water scarcity, and has outstanding drought resistance. In this study, Illumina sequencing was used to obtain the complete sequence of the S. varia chloroplast genome. The complete genome was 154, 257 bp in length with 35.9% GC content. It was a circular genome containing a large single-copy region (LSC, 84, 762 bp), a small single-copy region (SSC, 18, 059 bp), and a pair of inverted repeat regions (IRs, 51, 436 bp). A total of 128 genes were encoded, including 83 protein-coding genes, 37 tRNAs, and 8 rRNAs. Phylogenetic analysis revealed that S. varia was closely related to Robinia pseudoacacia . The sequence data of S. varia chloroplast genome could provide useful genetic information for the studies on phylogenetic and evolutionary of Leguminosae.